Exploring the relationship between soil moisture dynamics and postharvest losses in drought and flood-prone regions of the tropics: A review (Agriculture, Food, and Natural Resources Journal, 2025)
Soil moisture dynamics significantly influence agricultural productivity and postharvest losses, particularly in tropical regions prone to droughts and floods. Extreme moisture conditions negatively impact crop quality, storage potential, and food security, with droughts causing poor grain filling, increased pest infestations, and inefficient drying, while floods result in waterlogging, delayed harvesting, and contamination risks. This review explores the relationship between soil moisture variability and postharvest losses, highlighting the need for sustainable soil and water management strategies. Conservation agriculture, improved drainage systems, and postharvest technologies such as solar drying, hermetic storage, and AI-driven monitoring systems are critical in mitigating losses. Despite advancements, knowledge gaps remain in predictive modeling, localized soil moisture retention, and cost-effective postharvest solutions for smallholder farmers. Future research should focus on Artificial Intelligence-driven soil moisture forecasting, adaptive irrigation techniques, and resilient storage infrastructure. Additionally, policy frameworks must integrate climate adaptation strategies, research funding, and extension services to enhance farmer capacity. A multi-disciplinary approach involving governments, research institutions, and local communities is essential for implementing sustainable solutions. The integration of remote sensing, Geographic Information System (GIS), and AI technologies can improve real-time monitoring and decision-making in soil moisture management. Strengthening collaborations and investments in climate-smart agriculture will enhance food security and economic stability in tropical regions. This review highlights the pressing need for innovative, scalable, and region-specific interventions to mitigate postharvest losses resulting from soil moisture extremes.
Keywords: Adaptation; AI-driven monitoring; Climate; Remote sensing; Storage